Therapy-persistent leukemia is selectively vulnerable to SLC23A1 restoration via targeting KHSRP - Qingyu Luo; Karley S. Whalen; Xiaowei Wu; Amanda L. Fortune; Jacqueline S. Garcia; Kate Marinchev; Lin Zhang; Weiye Qian; Evangeline G. Raulston; Yabing Nan; Christopher A.G. Booth; Kezhi Yan; et al. (Blood Cancer Discovery, 2026)
Abstract Acute myeloid leukemia (AML) is prone to relapse driven by therapy-persistent residual cells. To discover specific vulnerabilities in this population, we performed genome-wide CRISPR interference screens in leukemia cells treated with multiple agents. KHSRP was the top hit, whose depletion sensitized AML cells to therapy and substantially prolonged survival in treated AML-bearing mice. Analysis of in vivo residual disease after venetoclax/azacitidine treatment identified downregulation of the vitamin C and uric acid transporter SLC23A1, which mediated resistance to multiple therapies. KHSRP depletion restored SLC23A1 expression by preventing its ZC3H4-mediated nuclear mRNA degradation. KHSRP depletion therefore enhanced the synergistic cytotoxicity of vitamin C and uric acid, particularly in therapy-persistent leukemia cells. Re-expression of TET2 overrode the chemosensitizing effect of KHSRP depletion in TET2-mutant leukemia, suggesting that KHSRP-linked phenotypes were related to vitamin C and uric acid-mediated TET activation. These findings nominate targeting KHSRP to enhance treatment efficacy and selectively eradicate residual AML.